(untitled) (Global Journal of Human-Social Science, 2017)
There is currently a need for a review of the definition and methodology of determining sustainable yield. The reasons are: (1) current definitions and concepts are ambiguous and nonphysically based so cannot be used for quantitative application, (2) there is a need to eliminate varying interpretations and misinterpretations and provide a sound basis for application, (3) the notion that all groundwater systems either are or can be made to be sustainable is invalid, (4) often there are an excessive number of factors bound up in the definition that are not easily quantifiable, (5) there is often confusion between production facility optimal yield and basin sustainable yield, (6) in many semi-arid and arid environments groundwater systems cannot be sensibly developed using a sustained yield policy particularly where ecological constraints are applied. Derivation of sustainable yield using conservation of mass principles leads to expressions for basin sustainable, partial (nonsustainable) mining and total (nonsustainable) mining yields that can be readily determined using numerical modelling methods and selected on the basis of applied constraints. For some cases there has to be recognition that the groundwater resource is not renewable and its use cannot therefore be sustainable. In these cases, its destiny should be the best equitable use. We suggest using the term Managed Yield as an alternative to Sustainable Yield to clarify the ambiguity among stakeholders.